The PPARG Pro12Ala Polymorphism and 20-year Cognitive Decline: Race and Sex Heterogeneity. (April 2018) - West, Nancy A.; Tingle, Jonathan V.; Simino, Jeannette; Selvin, Elizabeth; Bressler, Jan; Mosley, Thomas H.
Abstract : Previous reports suggest race/ethnic and sex heterogeneity in the association between the Pro12Ala polymorphism of the peroxisome proliferator-activated receptor gamma ( PPARG ) gene and cognitive decline. Tests of verbal memory, processing speed, and verbal fluency and a composite global Z -score were used to assess cognitive performance longitudinally in a large (n=11, 620) biracial cohort of older adults in the Atherosclerosis Risk in Communities Neurocognitive Study from midlife to older age. Linear mixed models were used to estimate associations between the Ala12 allele and cognitive performance over 20 years of follow-up. Heterogeneity was present for rate of cognitive decline as measured by the global Z -score by race, sex, and Ala12 allele status ( P =0.01 for 4-way interaction term: race×sex×time×Ala12 carrier status). Stratified analysis showed a significantly increased rate of global cognitive decline over the 20-year follow-up for carriers of the Ala12 allele compared with noncarriers among black male individuals (−0.92 SD decline vs. −0.57 SD; P =0.02) but not among black female, white male, or white female individuals. Decline in global cognitive function among black male Ala12 carriers was primarily driven by decline in verbal memory. Our data underscore the context-dependent association between the Pro12Ala polymorphism and cognitive decline, specifically race/ethnic background and sex.